Effect of pre-transplantation serum ferritin on outcomes in patients undergoing allogeneic hematopoietic stem cell transplantation: A meta-analysis. Issue 27 (July 2018) - Yan, Zhengwei; Chen, Xianying; Wang, Huiping; Chen, Yaling; Chen, Lihong; Wu, Peilin; Wang, Wei
Abstract: Background: Pre-transplantation serum ferritin (SF) has been considered to be a potential prognostic biomarker in patients undergoing allogeneic hematopoietic stem cell transplantation (allogeneic HSCT), but this conclusion remains controversial. Thus, we performed a meta-analysis to investigate the prognostic significance of pre-transplantation SF in patients undergoing allogeneic HSCT. Methods: We systematically searched PubMed, Embase, and Web of Science up to September 2017, and finally identified a total of 25 eligible studies with 4545 patients. Results: The pooled results of our meta-analysis showed that high pre-transplantation SF was markedly related to worse overall survival (OS) [hazard ratio (HR) = 1.82; 95% confidence interval (95% CI): 1.47–2.26; P  < .001], nonrelapse mortality (NRM) (HR = 2.28; 95% CI: 1.79–2.89; P  < .001), and progression-free survival (PFS) (HR = 1.72; 95% CI: 1.27–2.33; P  < .001). In addition, high pre-transplantation SF was closely associated with a lower incidence of chronic graft versus host disease (cGVHD) (OR = 0.74, 95% CI: 0.58–0.96; P  < .05), and a higher incidence of blood stream infections (BSIs) (OR = 1.67, 95% CI: 0.93–3.01; P  = .09). However, no significance relationship was found between elevated pre-transplantation SF and acute graft versus host disease (aGVHD) (OR = 1.08, 95% CI:.72–1.62; P  = .70). Conclusion: In patients undergoing allogeneic HSCT for hematological malignancies, elevated pre-transplantation SF was significantly associated with worse OS and PFS, higher incidence of NRM and BSI, and lower incidence of cGVHD, but it had no effect on aGVHD. Considering the limitations in our meta-analysis, more prospective and homogeneous clinical studies are needed to further confirm our findings.